Intersection of Jurisdiction in Resolving Sharia Banking Disputes in General Court: Titik Singgung Wewenang Penyelesaian Sengketa Perbankan Syariah di Peradilan Umum - Almaududi, Almaududi (Jurnal Konstitusi, 2024)
After the Constitutional Court Decision No.93/PUU-X/2012, there were still sharia banking disputes, which were resolved through the General Courts. As in the Padang District Court Decision No. 27/Pdt.G.S/2022/PN Pdg. This study aims to unravel the intersection of jurisdiction in resolving sharia banking disputes after Constitutional Court Decision. This study uses normative juridical methods. The results of the study show that after the Constitutional Court Decision, there is still legal uncertainty in the settlement of sharia banking disputes due to the existence of Article 50 paragraph (2) of the Law 7/1989 on Religious Courts. These provisions have resulted in a blurring of the points of contact for the authority to adjudicate the Religious Courts and the General Courts in resolving property rights disputes, unlawful acts disputes (PMH), and consumer disputes.